An ultra-sensitive dopamine photoelectrochemical sensing platform based on two-dimensional Zn carbon nanosheets, hollow Cu2O and CdTe QDs composite films. (15th October 2022) - Wang, Chenxi; Chen, Jia; Zhang, Li; Yang, Yaqi; Huang, Minghui; Chen, Chao; Li, Chunyan; Xie, Yixi; Zhao, Pengcheng; Fei, Junjie
Abstract: In this work, two-dimensional Zn carbon nanosheets (CNs) are obtained after heat treatment of in situ synthesized ZIF-8/NaCl nanocomposites, which are ultrasonically mixed with carboxylated multi-walled carbon nanotubes (MWCNTs). Subsequently, the nanocomposites Zn CNs-MWCNTs with large specific surface area and excellent catalytic properties are obtained. Meanwhile, the photoelectric material H–Cu2 O/CdTe QDs are drop-coated on Zn CNs-MWCNTs/GCE and the modified electrode Zn CNs-MWCNTs/H–Cu2 O/CdTe QDs/GCE is obtained. Eventually, a novel dopamine photoelectrochemical sensor based on Zn CNs-MWCNTs/H–Cu2 O/CdTe QDs/GCE is constructed. Among them, the photocurrent intensity of H–Cu2 O/CdTe QDs is much higher than that of pure H–Cu2 O and pure CdTe QDs. This is due to the effective combination of CdTe QDs and H–Cu2 O to form a p-p heterojunction, which can effectively suppress the recombination of electron-hole pairs. Subsequently, the working mechanism of the photoelectrochemical sensor is investigated in depth by the Kubelka-Munk model. At the same time, the photoelectrochemical sensor has reliable selectivity, stability, reproducibility and limit of detection (LOD = 0.3 nM), and also provides a new idea for the detection of dopamine. Graphical abstract: Image 1 Highlights: First application of hollow Cu2 O in the field of photoelectrochemical sensors. The composite materials exhibited satisfactory photochemical properties. This photoelectrochemical sensor has a lower limit of detection. The mechanism of the photoelectrochemical sensor is thoroughly investigated.